2011
DOI: 10.1111/j.1742-4658.2011.08204.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine stimulates the gene expression and processing of sterol regulatory element binding proteins, thereby increasing the expression of their target genes

Abstract: Here we show that the larger the amount of glutamine added to the medium, the more the expression of genes related to lipid homeostasis is promoted by the activation of sterol regulatory element binding proteins (SREBPs) at the transcriptional and post‐translational levels in human hepatoma HepG2 cells. Glutamine increases the mRNA levels of several SREBP targets, including SREBP‐2. The gene expression of SREBP‐1a, a predominant form of SREBP‐1 in most cultured cells and a target of the general transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Forty-eight h later, luciferase and -galactosidase activities were measured as described previously. 10) Normalized luciferase values were determined by dividing the luciferase activity by the -galactosidase activity.…”
Section: Methodsmentioning
confidence: 99%
“…Forty-eight h later, luciferase and -galactosidase activities were measured as described previously. 10) Normalized luciferase values were determined by dividing the luciferase activity by the -galactosidase activity.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study reported that inhibition of GLS by 968 led to decreased expression of a set of genes important for oncogenic growth, perhaps due to global changes in histone methylation [75]. Furthermore, work using HepG2 hepatoma cells revealed that the presence of glutamine facilitates the gene expression of SREBP targets, both by inducing SREBP-1a transcription and by stimulating SREBP processing [76]. …”
Section: Effects On Signaling Pathways and Gene Expressionmentioning
confidence: 99%
“…After treatment, cells and media were harvested, and immunoblotting was performed as described previously (15). Polyclonal anti-HNF4␣ (H-171) and anti-PGC1 (H-300) were obtained from Santa Cruz Biotechnology.…”
Section: Methodsmentioning
confidence: 99%